A case of metastatic non-teratoid ocular medulloepithelioma in an adult horse - Nascimento, Daniel Lúcio do; Carvalho, Gabriel Domingos; Nonato, Idelvânia dos Anjos; Salgado, Breno Souza (Brazilian Journal of Veterinary Pathology, 2021)
This case reports an eight-years-old horse that presented a unilateral tumor in the left ocular orbital region diagnosed onthe basis of clinical signs, gross anatomopathological and histopathological investigations. The affected area was exenterationand submitted to histopathological evaluation and was diagnosed as a non-teratoid medulloepithelioma. This is a rare ocularneoplasm that usually affects young individuals – and was composed by neuroepithelium arranged in tubules and Flexner-Wintersteiner rosettes without presence of heteroplastic components. The animals died and was submitted to post-mortemevaluation, revealing presence of medulloepithelioma metastases at the internal region of the head, lymph nodes, lungs, andliver. This neoplasm usually presents a benign frame; however, the case herein described shows that it can be highly malignantand aggressive since it can cause extensive lesions and spread metastases to visceral organs.